2003
DOI: 10.1046/j.1365-313x.2003.01863.x
|View full text |Cite
|
Sign up to set email alerts
|

The LKA gene is a BRASSINOSTEROID INSENSITIVE 1 homolog of pea

Abstract: SummaryBrassinosteroids (BRs) are growth-promoting plant steroid hormones, and in garden pea (Pisum sativum L.), the lka mutant is defective in BR perception. Here, we show that LKA encodes P. sativum BRI1 (PsBRI1), a homolog of BRI1, which is the Arabidopsis leucine-rich repeat receptor-like kinase/BR receptor. PsBRI1 was isolated by screening a pea cDNA library using Arabidopsis BRI1 cDNA as the probe. PsBRI1 is predicted to encode a 1188-amino-acid protein that has 78% similarity with Arabidopsis BRI1. Sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 55 publications
6
57
0
Order By: Relevance
“…As was the case in previous studies in pea Symons and Reid, 2003a) and Arabidopsis , BL levels were below detection limits in all of the tissue types studied (Tables I and III Comparative Distribution of BRs in Wild-Type, lka, and lkb Plants Nomura et al (1999) have previously reported that BR levels are elevated in whole shoots of lka mutant plants and reduced in whole shoots of lkb mutant plants, in comparison with the wild type. This is consistent with the finding that the lkb mutation blocks the biosynthesis of BRs, while the lka mutation causes impaired perception of these substances (Nomura et al, , 2003Schultz et al, 2001). In this study, we show that these changes in endogenous BRs in lka and lkb mutant plants (compared to the wild type) are consistent across a wide range of different shoot tissues and are not restricted to any specific location (Table III).…”
Section: Spatial Distribution Of Brs In Wild-type Plantssupporting
confidence: 88%
See 1 more Smart Citation
“…As was the case in previous studies in pea Symons and Reid, 2003a) and Arabidopsis , BL levels were below detection limits in all of the tissue types studied (Tables I and III Comparative Distribution of BRs in Wild-Type, lka, and lkb Plants Nomura et al (1999) have previously reported that BR levels are elevated in whole shoots of lka mutant plants and reduced in whole shoots of lkb mutant plants, in comparison with the wild type. This is consistent with the finding that the lkb mutation blocks the biosynthesis of BRs, while the lka mutation causes impaired perception of these substances (Nomura et al, , 2003Schultz et al, 2001). In this study, we show that these changes in endogenous BRs in lka and lkb mutant plants (compared to the wild type) are consistent across a wide range of different shoot tissues and are not restricted to any specific location (Table III).…”
Section: Spatial Distribution Of Brs In Wild-type Plantssupporting
confidence: 88%
“…In contrast, it has previously been reported that 100 ng of BL in 10 mL of ethanol, applied to the third leaf (including leaflets, stipules, and petioles) of various pea genotypes, results in increased growth of the fourth internode (Nomura et al, 1997(Nomura et al, , 2003, thus implying some movement of exogenous BRs from the leaf to the stem. However, due to the relatively large volume of ethanol used, we cannot exclude the possibility that the increase in growth came about because some of the applied BL came into contact with the surface of the fourth internode itself.…”
Section: Transport Of Exogenously Applied Radiolabeled Brsmentioning
confidence: 83%
“…This fragment, from the 3# part of the gene, contained an open reading frame of 401 amino acids and was 91.3% identical (at the amino acid level) to the BRI homolog from pea (accession no. AB104529; Nomura et al, 2003). This gene was therefore assigned as a putative grape BRI1 homolog (VvBRI1).…”
Section: Cloning Of Putative Grape Dwf1 and Bri1 Homologsmentioning
confidence: 99%
“…Mutations of BRI1 orthologs in rice, pea, and tomato cause BR insensitive dwarf phenotypes [37][38][39], suggesting highly conserved function of BRI1. Interestingly, the tomato BRI1 was shown to function as receptor for both BR and systemin, a small peptide involved in plant defense (reviewed by Wang and He, 2004 [40]).…”
Section: Tissue Specific Functions Of the Homologs Of Bri1 And Bak1mentioning
confidence: 99%